Live sound basics : The fundamentals of live sound engineering for beginners - Wallace, Ric (CreateSpace, 2013)
This book is about the fundamentals of live sound engineering and is intended to supplement the curriculum for the online classes at the Production Institute (www.productioninstitute.com/students). Nonetheless, it will be invaluable for beginning sound engineers and technicians anywhere who seek to expand their knowledge of sound reinforcement on their own. Written with beginners and novices in churches and convention centers in mind, this book starts by teaching you professional terminology and the processes of creating production related documents used to communicate with other sound engineers, vendors and venues. Subjects such as Signal Path and AC (alternating current) power safety and distribution are closely examined. These two subjects are closely related to the buzzing, humming and other noise related phenomena that often plague sound reinforcement systems. Chapters include an in-depth review of both analog and digital mixing consoles, their differences and similarities, and the gain structure fundamentals associated with the proper operation of either type of mixing console. Audio dynamic processors such as compressors, limiters and noise gates and their operation are explained in detail. Audio effects like delay and reverb are examined so that you can learn the basics of "sweetening" the mix to create larger and more emotive soundscapes and achieve studio-like outcomes in a live sound environment. Advanced mixing techniques, workflow, and the conventional wisdom used by professional audio engineers are explained so you don't have to spend years trying to figure out how these processes are achieved. Last but not least, a comprehensive review of acoustic feedback, and how to eliminate it from stage monitors and main speaker systems are detailed in a step by step process. This book will be especially helpful to volunteer audio techs in houses of worship, convention centers and venues of all types. It will bridge the gap between the on-the-job training that beginners receive and the knowledge and conventional wisdom that professional sound engineers employ in their daily routine.